Contribution of Mitochondrial DNA Variation to Chronic Disease in East Asian Populations - Sun, Dayan; Wei, Yang; Zheng, Hong-Xiang; Jin, Li; Wang, Jiucun (Frontiers in Molecular Biosciences, 2019)
Mitochondria are the main producers of energy in eukaryotic cells. Mitochondrial dysfunction is associated with specific mitochondrial DNA (mtDNA) variations (haplogroups), and these variations can contribute to human disease. East Asian populations show enrichment of many mitochondrial haplogroups, including A, B, D, G, M7, M8, M9, N9, R9, and exhibit half of the known haplogroups of worldwide. In this review, we summarize the current research in the field of mtDNA variation and associated disease in East Asian populations and discuss the physiological and pathological relevance of mitochondrial biology. mtDNA haplogroups are associated with various metabolic disorders ascribed to altered oxidative phosphorylation. The same mitochondrial haplogroup can show either a negative or positive association with different diseases. Mitochondrial dynamics, mitophagy, and mitochondrial oxidative stress, ultimately influence susceptibility to various diseases. In addition, mitochondrial retrograde signaling pathways may have profound effects on nuclear-mitochondrial interactions, affecting cellular morphology and function. Other complex networks including proteostasis, mitochondrial unfolded protein response and reactive oxygen species signaling may also play pivotal roles in metabolic performance.